On the Г-compactness of integral functionals with degenerate locally Lipschitz integrands and varying domains of definition - Kovalevsky, A.A.; Rudakova, O.A. (Труды Института прикладной математики и механики, 2012)
In this Note, we announce a new Г-compactness result for a sequence of integral functionals defined on varying weighted Sobolev spaces. The result concerns the case where the degenerate integrands of the functionals satisfy a local Lipschitz condition but in general may not be convex with respect to the variable corresponding to the gradient of functions from domains of definition of the functionals. В заметке анонсирован новый результат о Г-компактности последовательности интегральных функционалов, определенных на переменных весовых пространствах Соболева. Этот результат относится к случаю, когда вырождающиеся интегранты функционалов удовлетворяют локальному условию Липшица, но, вообще говоря, могут не быть выпуклыми относительно переменной, соответствующей градиенту функций из областей определения функционалов. В замiтцi анонсований новий результат про Г-компактнiсть послiдовностi iнтегральних функцiоналiв, визначених на змiнних вагових просторах Соболєва. Цей результат належить випадку, коли вироднi iнтегранти функцiоналiв задовольняють локальну умову Лiпшiца, але, взагалi кажучи, можуть не бути опуклими вiдносно змiнної, що вiдповiдає градiєнту функцiй з областей визначення функцiоналiв.